Investigations on Synergistic and Antioxidant Actions of Medicinal Plant- Based Biosynthesis of Zinc Oxide Nanoparticles Against E.coli and K. pneumonia Bacteria - Rashid, Farzana; Pervaiz, Iqra; Malik, Husna; Kanwal, Zakia; Rafique, Muhammad; Gillani, Syed Sajid A. (Combinatorial Chemistry & High Throughput Screening, 2022)
Introduction: Bacterial resistance to multiple drugs is increasing at an alarming rate in the current era and nanotechnology is one of the effective and novel approaches to overcome drug resistance. Methods: Zinc Oxide Nanoparticles (ZnO NPs) have stronger antibacterial activity and are regarded as bio-safe nanomaterial. The aim of the present study is to synthesize the ZnO NPs using Aloe vera leaves extract and to investigate the synergistic effects and antioxidant actions of biosynthesized ZnO NPs against gram-negative bacteria E.coli and K. pneumoniae. The synergistic effect of β-lactam antibiotics (meropenem and ciprofloxacin) was tested along with ZnO NPs using Kirby’s disc diffusion assay. The antioxidant activity was investigated by α, α-diphenyl-β- picrylhydrazyl (DPPH) method. Results: Results of the study revealed that the antibacterial activity of the selected antibiotics was much enhanced by ZnO NPs than the antibiotics alone. The resistant antibiotic (ciprofloxacin) became sensitive when combined with ZnO NPs. The antioxidant activity reveals that biosynthesized ZnO NPs possess significantly higher (p<0.05) antioxidant activity (77%). Conclusion: The findings reveal that biosynthesized ZnO NPs have a much more eco-friendly approach. It can act as a strong potentiator of β-lactam antibiotics and put forward the possibility to use them effectively in targeted drug delivery, pharmaceuticals and biomedical fields.
Keywords: gram negative bacteria